EFFECTS OF FAMILY SUPPORT AND MATERNAL PSYCHOLOGICAL ON EXCLUSIVE BREASTFEEDING - Jenica Hillary Eka Firnanda MCRP; Risa Etika; Pudji Lestari (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: Breastmilk is the best food that a mother can give to her baby from birth until the first 6 months of life to support growth and development during the first 1000 days of life. The success of exclusive breastfeeding is influenced by several factors. The purpose of this study is to analyze the support of family and mother to support exclusive breastfeeding. Method: This research method is cross sectional with a retrospective study design. The number of samples was 48. The independent variables were family and psychological assistance from the mother. The successful variable is exclusive breastfeeding. The research instrument used was a questionnaire. Data analysis using Fisher Exact statistical tests. Results: The results showed that there is no influence between family support and psychological of mother on the success of exclusive breastfeeding. Fisher Exact trial results related to family support for exclusive breastfeeding showed p = 0.339 (p> 0.05), psychological motivation of mothers towards exclusive breastfeeding showed p = 0.167 (p> 0.05). Conclusion: This data shows inappropriate between family support and psychological mother to exclusive breastfeeding.